Evidence of Regulatory Noncompliance with SEC Disclosure Rules on Auditor Changes. - Schwartz, Kenneth B.; Soo, Billy S. (The Accounting Review, 1996)
Abstract Identifies widespread noncompliance with Securities and Exchange Commission (SEC) regulations requiring prompt disclosure of auditor changes. Institutional setting; Effect of changes in regulatory regimes; Competency factors; Disclosure costs and incentives.